Modeling of the control logic of a UASS based on coefficient of variation spraying distribution analysis in an indoor flight simulator - Hanif, Adhitya Saiful; Han, Xiongzhe; Yu, Seung-Hwa; Han, Cheolwoo; Baek, Sun Wook; Lee, Chun-Gu; Lee, Dae-Hyun; Kang, Yeong Ho (Frontiers in Plant Science, 2023)
Introduction In the past decade, unmanned aerial spraying systems (UASS) have emerged as an effective crop treatment platform option, competing with other ground vehicle treatments. The development of this platform has provided an effective spraying system that can be used on all crop types and in all weather conditions. However, related research has not been able to develop a UASS that can be operated in windy conditions with a low drift percentage. Methods In this research, spraying was simulated in an indoor flight simulator by considering flight speed, altitude, wind speed, wind direction, rotor rotation, interval, spraying pattern, and nozzle type, which were used as the parameters affecting the output value of the coefficient of variation (CV) of spraying. These parameters were referenced as properties that occur in the field, and using machine learning methods, the CV value was used as a dataset to develop a model that can execute pump opening by controlling the flow rate. There are four machine learning methods used, i.e. random forest regression, gradient boosting, ada boost, and automatic relevance determination regression which are compared with simple linear regression and ridge regression as linear regression. Results The results revealed that the random forest regression model was the most accurate, with R2 of 0.96 and root mean square error (RMSE) of 0.04%. The developed model was used to simulate spraying with pump opening A, which connects two nozzles in front, and pump opening AB, which connects all four nozzles. Discussion Using the logic based on CV value and pesticide quantity, the model can execute the pump opening against the environment and UASS operation.